Komunikasi â€œLove Languageâ€ Dalam Keluarga (Studi Pada Pasangan Suami Istri Di Kelurahan Bukit Baru Palembang) - Nurmala Sari; Eni Murdiati; Muhammad Randicha Hamandia (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
ABSTRACT Love language communication is the language of love that everyone has for satisfaction in establishing a relationship within the family, which is expressed through actions or speech to their partner which includes words of affirmation (words of support), quality time (quality time), acts of service (service), receiving gifts (receiving gifts) and physical touch (physical touch) this theory was developed and proposed by Gary Chapman in 1992. The method used in this study is a qualitative method in which the author conducts interviews, documents and field observations. The purpose of this study is to find out what love language each partner has and how they express and communicate this love language to their partner through activities that are usually carried out to satisfy their partner in a relationship. The research results obtained in this study are regarding the communication carried out by husband and wife who are the object of communicating their love, which can vary both verbally and through signs, starting from helping the wife with work at home, encouraging her husband when going to work, spending time together. at home or outside, giving gifts, holding hands, hugging or communicating it by having sex between husband and wife. And the way husband and wife solve household problems can also be done by using the language of love that is owned by the couple and also discussed together to find problem points and solutions so that the problems that occur do not drag on. Keywords: Communication, Love Language, Family, and Husband and Wife